181 Transoesophageal atrial pacing stress echocardiography as a viable alternative to exercise and pharmacological stress echocardiography. (6th June 2022) - Stefil, Maria; Stefil, Svetlana
Abstract : Background: Pharmacological stress echocardiography (SE) is known to be associated with a higher risk of arrhythmias and haemodynamic instability compared to exercise SE. However, exercise SE poses challenges due to the procedural difficulty and low utility in patients with impaired mobility or reduced exercise tolerance due to non-cardiac pathologies. Transoesophageal atrial pacing SE (TOAPSE) is a minimally invasive technique that does not rely on patient agility, nor does it carry the risk of the adverse effects that are associated with pharmacological pacing. We examined the feasibility, safety, and patient tolerability of TOAPSE in 'real world' study. Methods: Consecutive patients with suspected ischaemic heart disease admitted to a regional hospital in eastern Estonia were enrolled in a prospective feasibility study from January 2020 to October 2020. Transoesophageal atrial overdrive pacing was performed using SEIVA EKG Praktik equipment sourced from Prague, Czech Republic. A head-to-head comparative analysis was performed in a subset of patients who underwent coronary angiography following TOAPSE. Significant coronary artery disease (CAD) was defined as the presence of ≥50% stenosis of one or more major epicardial vessels as evidenced by coronary angiography. Data on haemodynamic variables, duration of test, intra-procedural medications and patient assessment of tolerability were collected. Results: A total of 80 patients (66% male; mean age 63.3 +/- 8.79 years) were enrolled in the study, 53% of whom underwent both TOAPSE and coronary angiography (71% male; mean age 64 +/- 8.5). 24% patients were aged ≥70 years and 20% of patients had a history of myocardial infarction or revascularisation. Pacing was successful in 91% of patients, out of whom target peak heart rate (HR) (85% of the age-adjusted maximum HR) was achieved in all but one patient. We observed 66% agreement between TOAPSE and coronary angiography for identifying the culprit coronary artery territory with a Cohen's Kappa value of 0.12; the rate of agreement appeared to be higher among male patients (73% vs 50%, p=0.16). Sensitivity of TOAPSE for detecting patients with significant CAD was 96% (95% confidence interval [CI] 88–104), whilst specificity was 14% (95% CI -4–33). There were no documented ventricular or supraventricular tachyarrhythmias, nor any issues with hyper/hypotension associated with pacing (Table 1). Atropine was used in 42% and midazolam in 58% of patients at a mean dose of 1.1 ± 0.5 mg and 1.2 ± 0.4 mg respectively. The mean pacing threshold required was 15.8 ± 5.1 mA. The mean length of time required to reach target peak HR from placement of transoesophageal electrodes was 9.3 ± 4.3 min; mean recovery time from the end of pacing until the resolution of HR to within 10 beats of the baseline HR was 11.1 ± 4.5 min. Side effects, along with their relative severities, are displayed in Figure 1. Only one patient out of the whole cohort indicated that they would not be prepared to undergo the procedure again. Conclusion: TOAPSE effectively reproduces demand-driven myocardial ischaemia and is safe, quick, and well tolerated in all ages including older adults. We demonstrated high sensitivity with low specificity for detection of significant coronary artery disease which could be attributed to the small sample size and operator inexperience. In part, a high rate of false positive results could also be explained by a potentially high burden of microvascular coronary disease. Future studies comparing TOAPSE with magnetic resonance or positron emission tomography myocardial perfusion imaging are therefore warranted. The utility of TOAPSE should also be explored in the context of dynamic assessment and quantification of valve disease and myocardial viability testing. Conflict of Interest: None